Incorporation of biomass fly ash and biological sludge in the soil: effects along the soil profile and in the leachate water - Ribeiro, João Peres (2018)
Purpose This work aimed to study the effect of the application of biomass fly ash in the soil profile and percolate water, which is a novel feature. The results produced by this work pose a useful contribute for by-products’ valorization for the pulp and paper industry, namely fly ash and sludge, diverting them from landfills and achieving significant savings. Materials and methods Soil profiles (0.60 m) were collected in the field and into laboratory-scale vessels. Four soil profiles were used in this work. One of the profiles was used as control. To each of the other three, 7.5 Mg ha−1 of biomass fly ash, fly ash combined with sludge (50:50%wt.), or a conventional liming agent (CaO) were added. A simulation of the daily natural watering of the soils has been made throughout 1 month, with collection of the daily percolating from the bottom of the vessels. After this period, soil profiles were divided into three equal-sized depth layers (0.20 m each). Soil pH, electrical conductivity, and available Ca, Mg, K, P, Na, Mn, Fe, Zn, and Cu contents were determined in the three layers for each of the four soil profiles used. A parallel experiment was conducted in which additional pots of soil were prepared with the same amendment. Ryegrass (Lolium perenne) was sown in order to evaluate the effect on biomass growth and possible phytotoxicity. Results and discussion Amendment with biomass fly ash elevated soil pH slightly, to values within the most adequate range for plant growth. Results showed small raises in the availability of the essential plant macronutrients Ca, K, and Mg, especially in the top layer of the soils, where the amendment materials were applied. The mobilization of cations to the groundwater was always minimal, which is promising since it means little contamination to the groundwater. Ash and ash + sludge amendments produced similar plant growth results when compared to the control. However, biomass grown in Cao-amended pots showed the higher root size. Conclusions Incorporation in the soil proved to be a viable way to manage fly ash and sludge from pulp and paper industry, which could mean considerable savings. The effect on soil fertilization was similar to the conventional liming agent. No obvious hazardous effect on the soil or groundwater was found.